Back to SICAV. Critical reflection from an economic-tributary point of view - Luque, Víctor Antonio; Luque, Miguel Ángel (Papeles de Europa, 2014)
SICAVs are a type of investment society which are receiving "specific media attention" because, at least in appearance, they are an instrument which enables the channelling of investment by the large equities/net worths benefiting from a nominal type in corporate tax of only 1%. This paper analyses the patrimonial evolution and its distribution between the different components from 2001 to 2014. The possible existence of law fraud in the use of this figure is discussed, when instrumented by one or more people associated for the purpose of obtaining a tributary saving outside the object (collective investment) of society. The repercussions of the fact that competition for tributary control of the SICAV resides in the CNMV instead of the State Tributary Administration Agency is analysed. Finally, some observations regarding the potential risk of capital flight that has sometimes served as justification for the establishment of a privileged legal regime are presented.